Fedros ir Hipolito motyvas M. I. Cvetajevos laiškuose A. V. Bachrachui - Tuganova, Natalja (Literatūra, 2015)
The article deals with the antic code in letters by Marina Tsvetaeva to Alexandr Bachrach. Analyze is based on Lotmanean and his school works on intermediality. Lotmanean approach to the function and features of textual code gives firm ground to state, that characters’ structure of letters and their intra-textual links correspond to main features of theatrical code. These elements compose entities close to theatrical system of Antic theatre. Tsvetaeva does not call the roles of the participants of correspondence, but the totality of some elements of letters allows to speak about the recreation of the plot of Antic myth of “Fedra and Hippolit”.